Cardiomegaly and heart failure in a patient with prolactin-secreting pituitary tumour. Issue 3 (June 1979) - Curtarelli, G; Ferrari, C
Abstract : Unexplained cardiomegaly with cardiac failure was observed in a 42-year-old woman in whom a pituitary tumour had been treated by radiotherapy five years previously. She had been amenorrhoeic for 10 years. Thyroid and adrenal function was normal. Despite treatment with digitalis and diuretic, her cardiac disease progressed until she died suddenly at the age of 45. Hyperprolactinaemia was evident some weeks before death, her serum concentration of 68 ng/ml being well above both the reported normal range (2--20 ng/ml) and the concentrations in eight female controls being treated for severe cardiac failure (5--25 ng/ml). Although the association of these two disorders might merely represent coincidence, heart disease with similar features is common in acromegaly and does not correlate with plasma growth hormone concentration. Since prolactin is known to exert metabolic growth hormone-like effects in animals and in man, the possibility should be considered that prolactin hypersecretion might induce or maintain cardiac disease in some patients with pituitary tumours. A preliminary survey of 35 subjects with hyperprolactinaemia has shown five with raised blood pressure and four, two of whom were normotensive, with cardiomegaly on chest radiography.